Identification of Neutrophil Exocytosis Inhibitors (Nexinhibs), Small Molecule Inhibitors of Neutrophil Exocytosis and Inflammation: DRUGGABILITY OF THE SMALL GTPase Rab27a - Johnson, Jennifer L. (J Biol Chem, 2016)
Neutrophils constitute the first line of cellular defense in response to bacterial and fungal infections and rely on granular proteins to kill microorganisms, but uncontrolled secretion of neutrophil cargos is injurious to the host and should be closely regulated. Thus, increased plasma levels of neutrophil secretory proteins, including myeloperoxidase and elastase, are associated with tissue damage and are hallmarks of systemic inflammation. Here, we describe a novel high-throughput screening approach to identify small molecule inhibitors of the interaction between the small GTPase Rab27a and its effector JFC1, two central regulators of neutrophil exocytosis. Using this assay, we have identified small molecule inhibitors of Rab27a-JFC1 binding that were also active in cell-based neutrophil-specific exocytosis assays, demonstrating the druggability of Rab GTPases and their effectors. These compounds, named Nexinhibs (neutrophil exocytosis inhibitors), inhibit exocytosis of azurophilic granules in human neutrophils without affecting other important innate immune responses, including phagocytosis and neutrophil extracellular trap production. Furthermore, the compounds are reversible and potent inhibitors of the extracellular production of superoxide anion by preventing the up-regulation of the granule membrane-associated subunit of the NADPH oxidase at the plasma membrane. Nexinhibs also inhibit the up-regulation of activation signature molecules, including the adhesion molecules CD11b and CD66b. Importantly, by using a mouse model of endotoxin-induced systemic inflammation, we show that these inhibitors have significant activity in vivo manifested by decreased plasma levels of neutrophil secretory proteins and significantly decreased tissue infiltration by inflammatory neutrophils. Altogether, our data present the first neutrophil exocytosis-specific inhibitor with in vivo anti-inflammatory activity, supporting its potential use as an inhibitor of systemic inflammation.